How long is long enough, and have we done everything we should?—Ethics of calling codes. Issue 8 (23rd September 2014) - Ranola, Primi-Ashley; Merchant, Raina M; Perman, Sarah M; Khan, Abigail M; Gaieski, David; Caplan, Arthur L; Kirkpatrick, James N
Abstract : 'Calling' a code can be an ambiguous undertaking. Despite guidelines and the medical literature outlining when it is acceptable to stop resuscitation, code cessation and deciding what not to do during a code, in practice, is an art form. Familiarity with classic evidence suggesting most codes are unsuccessful may influence decisions about when to terminate resuscitative efforts, in effect enacting self-fulfilling prophesies. Code interventions and duration may be influenced by patient demographics, gender or a concern about the stewardship of scarce resources. Yet, recent evidence links longer code duration with improved outcomes, and advances in resuscitation techniques complicate attempts to standardise both resuscitation length and the application of advanced interventions. In this context of increasing clinical and moral uncertainty, discussions between patients, families and medical providers about resuscitation plans take on an increased degree of importance. For some patients, a 'bespoke' resuscitation plan may be in order.